Method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane

By introducing bismuth oxyhalide into PVDF-based solid electrolyte and using in-situ preparation method, safety problems and low conductivity caused by lithium dendrites' growth and side reactions are solved, and a composite solid electrolyte membrane with high cycling performance and uniform distribution is achieved.

CN119764551AActive Publication Date: 2025-04-04TIANMU LAKE INST OF ADVANCED ENERGY STORAGE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510169367.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-04
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The irregular growth and uncontrollable side reactions of lithium dendrites in traditional lithium-ion batteries lead to safety problems, and the ionic conductivity of PVDF-based solid electrolytes is low and easy to crystallize, affecting the cycling performance of the battery.

Method used

By introducing bismuth oxyhalide as an inorganic filler, the formation of pores in the composite solid electrolyte is limited, the transformation of the PVDF matrix to the β phase is promoted, and the formation of LiF is formed during the circulation process, thereby improving electrochemical performance. In-situ preparation method is adopted to ensure the uniform distribution of bismuth oxyhalide in the PVDF matrix.

Benefits of technology

It significantly improves the circulation efficiency and ionic conductivity of PVDF-based solid electrolytes, extends service life and improves overall performance, simplifies the preparation steps and improves efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005273451020000181
    Figure BDA0005273451020000181
  • Figure FDA0005273451010000021
    Figure FDA0005273451010000021
  • Figure FDA0005273451010000022
    Figure FDA0005273451010000022
Patent Text Reader

Abstract

The invention discloses a method for in-situ preparation of a bismuth oxyhalide-PVDF (polyvinylidene fluoride)-based composite solid electrolyte membrane, which comprises the following steps: respectively dissolving bismuth salt and organic halide containing alkyl and quaternary ammonium cations in an organic solvent in a heating state according to a stoichiometric ratio to obtain a solution 1 and a solution 2, and then preparing the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to the stoichiometric ratio to obtain the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane. The preparation method comprises the following steps: dissolving a polymer containing a PVDF chain segment and a lithium salt in a solution 2 containing a bismuth salt in a heating state to obtain a solution 3, mixing the solution 2 and the solution 3 in the heating state to react to obtain a precursor solution of the composite electrolyte, and coating and curing the precursor solution of the composite electrolyte to obtain the composite solid electrolyte. According to the preparation method provided by the invention, the problem that the cycle performance of the solid electrolyte is insufficient due to the fact that the bismuth oxyhalide inorganic filler is difficult to uniformly disperse in a polymer matrix is solved, and the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane can be rapidly prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid-state batteries, and in particular relates to a method for in-situ preparation of a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane. Technical Background

[0002] With the rapid advancement of technology, the widespread use of various electronic devices has made it impossible for traditional lithium-ion batteries (LIBs) to provide higher energy density. Lithium metal batteries (LMBs) have become a promising choice for the next generation of high-performance batteries due to their relatively high energy density and low reduction potential. However, the safety issues caused by the irregular growth of lithium dendrites and uncontrollable side reactions in traditional organic flammable liquid electrolytes (LEs) have hindered the development of LMBs.

[0003] Solid-state electrolytes (SSEs) have been identified as promising alternatives to LEs, with superior electrochemical stability and mechanical properties, which can address safety issues associated with Li dendrite growth and interfacial reactions. Among them, PVDF has received great attention due to its ideal mechanical strength, excellent thermal stability, wide voltage window, and excellent electrochemical stability. However, PVDF also has some inherent disadvantages, such as low ionic conductivity and easy crystallization, which may lead to lithium dendrites or even "dead lithium" phenomena during the battery cycle, thus affecting the battery's cycle performance.

[0004] In the study, we found that when bismuth oxyhalide is introduced into the PVDF matrix as an inorganic filler, the bismuth oxyhalide can compete with the phase change process of the polymer containing polyvinylidene fluoride segments during the curing process, thereby limiting the formation of pores in the composite solid electrolyte; secondly, in the process of competing for phase change, bismuth oxyhalide can promote the polymer containing polyvinylidene fluoride segments to transform into the β phase, and promote the polymer containing polyvinylidene fluoride groups to form LiF during the cycle process, improving the cycle performance and ionic conductivity of the PVDF matrix, so it is expected to be used as an inorganic filler to improve the electrochemical performance of the PVDF matrix. However, since bismuth oxyhalide is composed of bismuth oxygen layers and halogen layers arranged alternately, its unique layered structure makes the bismuth oxyhalide particles have strong interlayer forces. When mixed with the solid electrolyte precursor solution, there are often problems such as uneven mixing and agglomeration of bismuth oxyhalide. This uneven mixing method will lead to uneven lithium ion transmission in the prepared composite solid electrolyte and serious side reactions in some areas of the membrane, thereby affecting the long cycle performance of the battery.

[0005] How to further improve the preparation process, simplify the preparation process and improve the preparation efficiency based on obtaining a uniform bismuth oxyhalide-PVDF matrix composite solid electrolyte has become the focus of current research. Summary of the invention

[0006] The present invention aims at the problems in the prior art and proposes a method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, which solves the problems of uneven solid electrolyte lithium ion transmission, serious side reactions in some areas of the membrane, insufficient cycle performance, etc. caused by the difficulty in dispersing bismuth oxyhalide, and obtains a method for preparing bismuth oxyhalide-PVDF-based composite solid electrolyte membrane with high cycle performance.

[0007] In a first aspect, the present invention provides a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, wherein the raw materials include bismuth salt, organic halide containing alkyl and positively charged quaternary ammonium cations, polymer containing PVDF segments, and lithium salt, wherein the general formula of bismuth oxyhalide is BiOX, wherein Bi is bismuth element, O is oxygen element, X is halogen element, halogen element is selected from any one of Cl, Br, I, and F, and the mass ratio of bismuth oxyhalide to polymer containing PVDF segments is selected from (0.01-0.5): 1;

[0008] The beta phase percentage of PVDF in the in-situ prepared bismuth oxyhalide-PVDF-based composite solid electrolyte membrane is selected from 60% to 70%, and the crystallinity is 20% to 25%.

[0009] As a further solution, the bismuth oxyhalide is selected from any one of BiOCl, BiOBr, BiOI, and BiOF.

[0010] As some preferred schemes, the bismuth oxyhalide is selected from BiOCl.

[0011] As a further solution, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.5V.

[0012] As a further solution, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.6V.

[0013] As some preferred solutions, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.7V.

[0014] In a second aspect, the present invention provides a method for in-situ preparation of a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, comprising the following steps:

[0015] S1: dissolving a bismuth salt and an organic halide containing an alkyl group and a quaternary ammonium cation in an organic solvent respectively under heating according to a stoichiometric ratio to obtain a solution 1 and a solution 2;

[0016] S2: dissolving a polymer containing a PVDF segment and a lithium salt in solution 2 in a heated state according to a stoichiometric ratio to obtain solution 3;

[0017] S3: After mixing and reacting solution 1 and solution 3 under heating, a precursor solution of a composite electrolyte is obtained, and the precursor solution of the composite electrolyte is coated and cured to obtain a composite solid electrolyte membrane.

[0018] As a further solution, in step S1, the molar ratio of the bismuth salt to the organic halide containing an alkyl group and a quaternary ammonium cation is selected from 1:(2-2.5).

[0019] As a further solution, in step S1, the mass ratio of the total mass of the bismuth salt and the organic halide containing alkyl and quaternary ammonium cations to the organic solvent is selected from (0.01-0.5): (5-20).

[0020] As a further solution, in step S1, the bismuth salt is selected from any one of an oxygen-containing acid bismuth salt and an organic acid bismuth salt.

[0021] As a further solution, in step S1, the organic halide containing an alkyl group and a quaternary ammonium cation is selected from any one of the organic halide containing a C2-C20 alkyl group and a quaternary ammonium cation.

[0022] As a further solution, in step S1, the organic halide containing a C2-C20 alkyl group and a quaternary ammonium cation is selected from an organic halide having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation.

[0023] As a further solution, in step S1, the organic halide having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is selected from an ammonium halide salt having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation.

[0024] As a further solution, in step S1, the ammonium halide salt having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is not limited in principle, and can be selected from, for example, dioctadecyl dimethyl ammonium chloride Didodecyl dimethyl ammonium chloride Dimethylditetradecylammonium chloride Dioctadecyl dimethyl ammonium bromide Dimethyldioctadecylammonium iodide Tetrabutylammonium chloride Tetrapentylammonium chloride Tetrabutylammonium iodide Tetrahexylammonium iodide Tetraheptylammonium iodide Any one of .

[0025] As some preferred parameters, in the step S1, when the bismuth salt and the organic halide containing an alkyl group and a quaternary ammonium cation are respectively dissolved in an organic solvent, the heating temperature is selected from 40° C. to 50° C.

[0026] As a further solution, in step S2, the mass ratio of the polymer containing PVDF segments to the lithium salt is selected from 1:(0.25-2).

[0027] As a further embodiment, the mass ratio of the polymer containing PVDF segments to the organic solvent is selected from 1:(5-20).

[0028] As a further embodiment, the polymer containing PVDF segments is selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and a mixture of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).

[0029] As a further solution, in the mixture of PVDF and PVDF-HFP, the mass ratio of PVDF to PVDF-HFP is selected from 3:1.

[0030] As a further embodiment, the lithium salt is selected from any one or more of LiPF6, LiF, LiBF4, LiTFSI, LiCl, Li2SO4, LiOAc, LiNO3, LiPO2F2, LiCF3SO3, Li2CO3, LiFSI, LiBOB, and LiDFOB.

[0031] As a further embodiment, the lithium salt is selected from LiTFSI.

[0032] As a further solution, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents, and ether solvents.

[0033] As some preferred parameters, in step S2, when the polymer containing PVDF segments and lithium salt are dissolved in solution 1 containing bismuth salt, the heating temperature is selected from 40° C.-50° C., and the heating time is greater than or equal to 6 hours.

[0034] As some preferred parameters, in step S2, when the polymer containing PVDF segments and lithium salt are dissolved in solution 1 containing bismuth salt, the heating temperature is selected from 40° C.-50° C., and the heating time is selected from 6 h-10 h.

[0035] As some preferred parameters, in step S3, the temperature for the mixed reaction of solution 1 and solution 3 is selected from 40°C-50°C, and the mixed reaction time is selected from 22h-26h.

[0036] As a further solution, in step S3, the coating method is not limited in principle, and the technicians can select a corresponding coating method according to the needs, such as mechanical coating.

[0037] As a further solution, the mechanical coating step is: pouring the solution 3 onto a glass plate, and then adjusting the scraper thickness to 300 μm for uniform coating.

[0038] As a further solution, the curing time is selected from 1.5h-3h.

[0039] As a further solution, the vacuum drying temperature in step S3 is selected from 60°C-80°C.

[0040] As a further solution, the vacuum drying time in step S3 is selected to be greater than or equal to 20 hours.

[0041] In a third aspect, the present solution provides a battery, comprising a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane prepared by a method for in-situ preparation of a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane.

[0042] As a further solution, the battery is selected from any one of a solid-state battery and a semi-solid-state battery.

[0043] As a further solution, the battery includes a positive electrode sheet and a negative electrode sheet.

[0044] As a further solution, the positive electrode sheet includes a positive electrode active material, a positive electrode current collector, a positive electrode conductor, and a positive electrode adhesive.

[0045] As a further solution, the positive electrode active material is selected from LiMO2, lithium nickel cobalt manganese oxide LiNi x Mn y Co z O2, LiNi p Co q Al f O2, lithium-rich manganese-based positive electrode material: Li 1+a Ni b Co c Mn d TM 1-b-c-d O2, Lithium Nickel Manganese Oxide Li k XO2, Lithium manganese iron phosphate Li e Mn 1-g-j Fe g Z jPO4, wherein M is selected from any one of Co, Li, and Mn, TM is selected from any one or more of nickel, cobalt, manganese, iron, titanium, chromium, vanadium, molybdenum, magnesium, and copper; X is selected from at least one of Ni, Co, and Mn. Z is selected from at least one of B, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni, Cu, Zn, Y, Zr, Nb, and Mo, 0.1≤x≤0.8, 0.1≤y≤0.3, 0.1≤z≤0.3, x+y+z=1, 0.6≤p≤0.9, 0.05≤q≤0.2, 0.03≤f≤0.1, 0 <a≤0.5,0<b≤0.3,0<c≤0.3,0.2<d≤0.7,0<k<1,1-b-c-d≥0,0.8<e<1.2,0.5<1-g-j<1,0.05<g<0.5,0<j<0.2。

[0046] As a further embodiment, the positive electrode current collector is selected from copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, alloys containing one or more of these, and one or more metals selected from alloys can be mentioned;

[0047] As a further solution, the positive electrode conductor is selected from any one or more of carbon materials, metal materials, and conductive polymers.

[0048] As a further solution, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0049] As a further solution, the negative electrode plate includes a negative electrode active material, a negative electrode current collector, a negative electrode conductive agent, and a negative electrode binder.

[0050] As a further embodiment, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , one or more of Li-Al alloys

[0051] As a further solution, the negative electrode current collector is not limited in principle, and for example, any one of aluminum, nickel, tin, copper and stainless steel can be selected.

[0052] As a further solution, the negative electrode conductive agent is selected from carbon materials.

[0053] As a further solution, the carbon material used as the negative electrode conductive agent is selected from any one or more of carbon black, Super P, activated carbon, graphite, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon fibers, conductive carbon black, carbon nanospheres, ellipsoidal carbon, hard carbon, amorphous carbon, and silicon carbide.

[0054] As a further solution, the negative electrode binder is selected from any one or more of polymers, rubbers, cellulose derivatives, and resins.

[0055] In a fourth aspect, the present invention provides an energy storage device composed of a plurality of batteries for storing and releasing electrical energy.

[0056] Compared with the prior art, the present invention has at least the following beneficial effects:

[0057] The present invention significantly improves the cycle efficiency and ionic conductivity of PVDF-based solid electrolytes by introducing bismuth oxyhalide as an inorganic filler, prolongs the service life and improves the overall performance. By incorporating bismuth oxyhalide precursors into a polymer matrix and achieving in-situ generation of bismuth oxyhalide during stirring, the bismuth oxyhalide is ensured to be uniformly distributed in the PVDF matrix, thereby effectively improving the dispersibility of the filler and solving the problem of easy agglomeration of bismuth oxyhalide. At the same time, the method provided by the present invention simplifies the preparation steps, improves efficiency, shortens the preparation time, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0059] Figure 1 XRD pattern of BiOCl synthesized in Comparative Example 1;

[0060] Figure 2 The XRD pattern of the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane synthesized in Example 1;

[0061] Figure 3 middle, Figure 3 a is solution 1, Figure 3 b is solution 2, Figure 3 c is a mixed solution of solution 1 and solution 2, Figure 3 d is the mixed solution of solution 1 and solution 2 after standing for 5 h;

[0062] Figure 4 This is the cycle diagram of Example 1 at 0.5C.

[0063] Figure 5 This is the electrochemical window diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0064] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.

[0065] The following is a description of terms or words, and unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0066] As used herein, the term "bismuth oxyhalide" refers to a product obtained by chemically reacting a bismuth salt, an organic halide containing an alkyl group and a quaternary ammonium cation.

[0067] In a first aspect, the present invention provides a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, wherein the raw materials include bismuth salt, organic halide containing alkyl and quaternary ammonium cations, polymer containing PVDF segments, and lithium salt, wherein the general formula of bismuth oxyhalide is BiOX, wherein Bi is bismuth element, O is oxygen element, X is halogen element, halogen element is selected from any one of Cl, Br, I, and F, and the mass ratio of bismuth oxyhalide to polymer containing PVDF segments is selected from (0.01-0.5): 1;

[0068] The beta phase percentage of PVDF in the in-situ prepared bismuth oxyhalide-PVDF-based composite solid electrolyte membrane is selected from 60% to 70%, and the crystallinity is 20% to 25%.

[0069] As some optional parameters, the bismuth oxyhalide is selected from any one of BiOCl, BiOBr, BiOI and BiOF.

[0070] As some preferred parameters, the bismuth oxyhalide is selected from BiOCl.

[0071] As some optional parameters, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.5V.

[0072] As some optional parameters, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.6V.

[0073] As some preferred parameters, the oxidation potential of the polyvinylidene fluoride-based composite solid electrolyte membrane is greater than or equal to 4.7V.

[0074] In a second aspect, the present invention provides a method for in-situ preparation of a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, comprising the following steps:

[0075] S1: dissolving a bismuth salt and an organic halide containing an alkyl group and a quaternary ammonium cation in an organic solvent respectively under heating according to a stoichiometric ratio to obtain a solution 1 and a solution 2;

[0076] S2: dissolving a polymer containing a PVDF segment and a lithium salt in solution 2 in a heated state according to a stoichiometric ratio to obtain solution 3;

[0077] S3: After mixing and reacting solution 1 and solution 3 under heating, a precursor solution of a composite electrolyte is obtained, and the precursor solution of the composite electrolyte is coated and cured to obtain a composite solid electrolyte membrane.

[0078] In order to optimize the performance of PVDF-based solid electrolytes, inorganic fillers were introduced into the PVDF matrix. During the experiment, we found that compared with inorganic fillers such as SiO2 and TiO2, the use of bismuth oxyhalides as inorganic fillers can effectively optimize the electrochemical performance of PVDF-based composite solid electrolyte membranes and improve the cycle efficiency and ionic conductivity. This may be because during the curing process of the composite solid electrolyte membrane, bismuth oxyhalides will compete with polymers containing polyvinylidene fluoride segments for phase change, thereby effectively inhibiting the formation of pores. In addition, during the phase change competition process, bismuth oxyhalides can promote the transformation of polymers from other phases to the β phase, and promote the formation of LiF in polyvinylidene fluoride groups during the cycle. This not only improves the cycle performance of the PVDF matrix, but also improves its ionic conductivity. Therefore, bismuth oxyhalides are expected to be used as an inorganic filler to significantly improve the electrochemical properties of the PVDF matrix.

[0079] However, during the experiment, we also found that it is not easy to achieve uniform dispersion of bismuth oxyhalide in the PVDF matrix. The existing preparation methods are often very complicated, and the preparation efficiency is low and time-consuming. Therefore, this scheme proposes a preparation method for a composite solid electrolyte membrane, which utilizes the characteristics that bismuth salt and organic halide containing alkyl and quaternary ammonium cations can be dissolved in organic solvents under heating conditions (40°C-60°C). Under heating conditions, bismuth salt and organic halide containing alkyl and quaternary ammonium cations are respectively dissolved in organic solvents, and polymer containing PVDF segments and lithium salt are further added to solution 2. Subsequently, solution 1 and solution 2 are mixed to achieve in-situ growth of bismuth oxyhalide in the matrix material, thereby obtaining a composite solid electrolyte membrane with uniform distribution of bismuth oxyhalide. In this scheme, organic halide containing alkyl and quaternary ammonium cations can not only induce bismuth salt to generate bismuth oxyhalide, but also the alkyl and quaternary ammonium cations in its structure can act as a surfactant, which further promotes the generation of bismuth oxyhalide while generating bismuth oxyhalide. Dispersion of bismuth; secondly, in this scheme, the bismuth salt and the organic halide containing alkyl and quaternary ammonium cations are dissolved in an organic solvent respectively to avoid the premature generation of bismuth oxyhalide, and at the same time, the dissolution of bismuth salt and the organic halide containing alkyl and quaternary ammonium cations is better achieved. Secondly, after the organic halide containing alkyl and quaternary ammonium cations is dissolved in an organic solvent to obtain solution 2, the polymer containing PVDF segments and lithium salt are further added to solution 2 in this scheme. This is because compared with solution 1, after the polymer containing PVDF segments and lithium salt are added to solution 2, the polymer containing PVDF segments can form a mutually interlaced uniform Internet structure with the organic halide containing alkyl and quaternary ammonium cations, so that the subsequent bismuth oxyhalide can be directly anchored and generated on the Internet structure, thereby achieving uniform distribution of bismuth oxyhalide in the composite solid electrolyte membrane. Finally, this scheme fully mixes solutions 1 and 3 and reacts and solidifies, that is, a composite solid electrolyte membrane with uniform distribution of bismuth oxyhalide is obtained, and a simple and efficient preparation method is provided.

[0080] As some optional parameters, in step S1, the molar ratio of the bismuth salt to the organic halide containing an alkyl group and a quaternary ammonium cation is selected from 1:(2-2.5). When the molar ratio of the bismuth salt to the organic halide containing an alkyl group and a quaternary ammonium cation is selected from 1:(2-2.5), the bismuth salt can be fully reacted.

[0081] As some optional parameters, in step S1, the mass ratio of the total mass of the bismuth salt and the organic halide containing alkyl and quaternary ammonium cations to the organic solvent is selected from (0.01-0.5): (5-20).

[0082] As some optional parameters, in step S1, the bismuth salt is selected from any one of oxygen-containing acid bismuth salts and organic acid bismuth salts.

[0083] As some optional parameters, the oxygen-containing acid bismuth salt is selected from any one of bismuth nitrate pentahydrate, bismuth sulfate, bismuth phosphate and bismuth carbonate.

[0084] As some optional parameters, the organic acid bismuth salt is selected from any one of bismuth acetate, bismuth citrate and bismuth oxalate.

[0085] As some optional parameters, in step S1, the organic halide containing an alkyl group and a quaternary ammonium cation is selected from any one of the organic halide containing a C2-C20 alkyl group and a quaternary ammonium cation.

[0086] As some optional parameters, in the step S1, the organic halide containing C2-C20 alkyl and quaternary ammonium cation is selected from an organic halide having structural symmetry and containing C4-C20 alkyl and quaternary ammonium cation. Asymmetric molecules tend to form irregular aggregates more easily, resulting in low local solubility or uneven distribution. Symmetrical structures can effectively avoid this situation. Therefore, in this scheme, an organic halide having structural symmetry and containing C4-C20 alkyl and quaternary ammonium cation is selected to help fully avoid local excessive aggregation of bismuth salts, thereby further improving the dispersion of bismuth oxyhalide in the matrix.

[0087] As some optional parameters, in step S1, the organic halide having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is selected from ammonium halide salts having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation.

[0088] As some optional parameters, in step S1, the ammonium halide salt having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is not limited in principle, for example, it can be selected from dioctadecyl dimethyl ammonium chloride Didodecyl dimethyl ammonium chloride Dimethylditetradecylammonium chloride Dioctadecyl dimethyl ammonium bromide Dimethyldioctadecylammonium iodide Tetrabutylammonium chloride Tetrapentylammonium chloride Tetrabutylammonium iodide Tetrahexylammonium iodide Tetraheptylammonium iodide Any one of .

[0089] As some preferred parameters, in the step S1, when the bismuth salt and the organic halide containing an alkyl group and a quaternary ammonium cation are respectively dissolved in an organic solvent, the heating temperature is selected from 40° C. to 50° C.

[0090] As some optional parameters, in step S2, the mass ratio of the polymer containing PVDF segments to the lithium salt is selected from 1:(0.25-2).

[0091] As some optional parameters, the mass ratio of the polymer containing PVDF segments to the organic solvent is selected from 1:(5-20).

[0092] As some optional parameters, the polymer containing PVDF segments is selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and a mixture of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).

[0093] As some optional parameters, in the mixture of PVDF and PVDF-HFP, the mass ratio of PVDF to PVDF-HFP is selected from 3:1.

[0094] As some optional parameters, the lithium salt is selected from any one or more of LiPF6, LiF, LiBF4, LiTFSI, LiCl, Li2SO4, LiOAc, LiNO3, LiPO2F2, LiCF3SO3, Li2CO3, LiFSI, LiBOB, and LiDFOB.

[0095] As some optional parameters, the lithium salt is selected from LiTFSI.

[0096] As some optional parameters, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents and ether solvents.

[0097] As some optional parameters, the amide solvent is selected from any one or more of N,N-dimethylformamide (DMF), N,N-diethylformamide (DEMF), N,N-dimethylpropionamide (DMPA), N-methyl-N-ethylformamide (MEMA), N-ethyl-N-methylformamide (EMEA), N-phenylpropionamide (NPA), N-ethyl-N,N-dimethylformamide (EDMF), and N,N-dimethylphthalamide (DMPhF).

[0098] As some optional parameters, the pyrrolidone solvent is selected from N-methylpyrrolidone (NMP), N-ethylpyrrolidone (NEP), N-butylpyrrolidone (NBP), N-isopropylpyrrolidone (NIP), N-octylpyrrolidone (NSP), N-hexadecylpyrrolidone (C 16 -Pyrrolidone), N-methyl-2-pyrrolidone (NMP-2), N,N-dimethyl-2-pyrrolidone (DM-2P) or any one or more thereof.

[0099] As some optional parameters, the ether solvent is selected from any one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), tetrahydrofuran (THF), dimethoxyethane (DME), ethoxyethane (EOE), ethylene oxide (EO), and phenyl ether.

[0100] As some preferred parameters, in step S2, when the polymer containing PVDF segments and lithium salt are dissolved in solution 1 containing bismuth salt, the heating temperature is selected from 40° C.-50° C., and the heating time is greater than or equal to 6 hours.

[0101] As some preferred parameters, in step S2, when the polymer containing PVDF segments and lithium salt are dissolved in solution 1 containing bismuth salt, the heating temperature is selected from 40° C.-50° C., and the heating time is selected from 6 h-10 h.

[0102] As some preferred parameters, in step S3, the temperature for the mixed reaction of solution 1 and solution 3 is selected from 40°C-50°C, and the mixed reaction time is selected from 22h-26h.

[0103] As some optional parameters, in step S3, the coating method is not limited in principle, and the technicians can select the corresponding coating method according to the needs, such as mechanical coating.

[0104] As some optional parameters, the mechanical coating step is: pouring solution 3 on a glass plate, and then adjusting the scraper thickness to 300 μm for uniform coating.

[0105] As some optional parameters, the curing time is selected from 1.5h-3h.

[0106] As some optional parameters, the vacuum drying temperature in step S3 is selected from 60°C-80°C.

[0107] As some optional parameters, the vacuum drying time in step S3 is selected to be greater than or equal to 20 hours.

[0108] In a third aspect, the present solution provides a battery, comprising a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane prepared by a method for in-situ preparation of a bismuth oxyhalide-PVDF-based composite solid electrolyte membrane.

[0109] As some optional parameters, the battery is selected from any one of a solid-state battery and a semi-solid-state battery.

[0110] As some optional parameters, the battery includes a positive electrode sheet and a negative electrode sheet.

[0111] As some optional parameters, the positive electrode sheet includes a positive electrode active material, a positive electrode current collector, a positive electrode conductive agent, and a positive electrode adhesive.

[0112] As some optional parameters, the positive electrode active material is selected from LiMO2, lithium nickel cobalt manganese oxide LiNi x Mn y Co z O2, LiNi p Co q Al f O2, lithium-rich manganese-based positive electrode material: Li 1+a Ni b Co c Mn d TM 1-b-c-d O2, Lithium Nickel Manganese Oxide Li k XO2, Lithium manganese iron phosphate Li e Mn 1-g-j Fe g Z j PO4, wherein M is selected from any one of Co, Li, and Mn, TM is selected from any one or more of nickel, cobalt, manganese, iron, titanium, chromium, vanadium, molybdenum, magnesium, and copper; X is selected from at least one of Ni, Co, and Mn. Z is selected from at least one of B, Mg, Al, Si, Ca, Ti, V, Cr, Co, Ni, Cu, Zn, Y, Zr, Nb, and Mo, 0.1≤x≤0.8, 0.1≤y≤0.3, 0.1≤z≤0.3, x+y+z=1, 0.6≤p≤0.9, 0.05≤q≤0.2, 0.03≤f≤0.1, 0 <a≤0.5,0<b≤0.3,0<c≤0.3,0.2<d≤0.7,0<k<1,1-b-c-d≥0,0.8<e<1.2,0.5<1-g-j<1,0.05<g<0.5,0<j<0.2。

[0113] As some optional parameters, the positive electrode current collector is selected from copper, aluminum, titanium, nickel, tantalum, niobium, hafnium, zirconium, zinc, tungsten, bismuth, antimony, gold, silver, iron, platinum, chromium, tin, indium, alloys containing one or more of these, and one or more metals selected from alloys can be mentioned.

[0114] As some optional parameters, the positive electrode conductor is selected from any one or more of carbon materials, metal materials, and conductive polymers.

[0115] As some optional parameters, the carbon material is selected from any one or more of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, and carbon fiber.

[0116] As some optional parameters, the metal material is selected from any one or more of copper, nickel, aluminum and silver.

[0117] As some optional parameters, the conductive polymer is selected from one or more of polyfluorene (PF), polyaniline (PANI), polypyrrole (PPy), polythiophene (PTh), polyethylene dioxythiophene (PEDOT), polyethylene dioxythiophene:polystyrene sulfonate (PEDOT:PSS), and polyacetylene (PA).

[0118] As some optional parameters, the positive electrode binder is selected from at least one of thermoplastic resin, acrylic resin, sodium carboxymethyl cellulose and styrene butadiene rubber.

[0119] As a further embodiment, the thermoplastic resin includes at least one of polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, polyethylene and polypropylene.

[0120] As some optional parameters, the negative electrode plate includes a negative electrode active material, a negative electrode current collector, a negative electrode conductive agent, and a negative electrode binder.

[0121] As some optional parameters, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , one or more of Li-Al alloys

[0122] As some optional parameters, the negative electrode current collector is not limited in principle, for example, any one of aluminum, nickel, tin, copper and stainless steel can be selected.

[0123] As some optional parameters, the negative electrode conductive agent is selected from carbon materials.

[0124] As some optional parameters, the carbon material used as the negative electrode conductive agent is selected from any one or more of carbon black, Super P, activated carbon, graphite, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes, carbon fibers, conductive carbon black, carbon nanospheres, ellipsoidal carbon, hard carbon, amorphous carbon, and silicon carbide.

[0125] As some optional parameters, the negative electrode binder is selected from any one or more of polymers, rubbers, cellulose derivatives, and resins.

[0126] As some optional parameters, the polymer is selected from any one or more of polyvinyl alcohol, polyvinyl chloride, polyvinyl fluoride, polyvinylidene fluoride, polyvinyl pyrrolidone, polyethylene, polypropylene, polyimide, polyacrylic acid, polyvinyl chloride, polytetrafluoroethylene, and polyvinylidene fluoride.

[0127] As some optional parameters, the rubber is selected from any one or more of styrene-butadiene rubber, EPDM rubber, and fluororubber.

[0128] As some optional parameters, the cellulose derivatives are selected from any one or more of carboxymethyl cellulose, hydroxypropyl cellulose and diacetyl cellulose.

[0129] As some optional parameters, the resin is selected from any one or more of epoxy resin and styrene.

[0130] In a fourth aspect, the present invention provides an energy storage device composed of a plurality of batteries for storing and releasing electrical energy.

[0131] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application and do not represent all possible embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0132] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0133] Example 1

[0134] S1: BiOCl was prepared by using dioctadecyl dimethyl ammonium chloride (DODAC) and bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), PVDF was used as the polymer containing PVDF segments, 0.1 g of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) was weighed and dissolved in 2.5 g of DMF at 45°C to obtain solution 1, and 0.27 g of dioctadecyl dimethyl ammonium chloride (DODAC) was weighed and dissolved in 5 g of DMF at a constant temperature of 45°C to obtain solution 2;

[0135] S2: 0.5 g of PVDF and 0.5 g of LiTFSI were added to solution 2, and then stirred at 45 °C for 6 h to obtain solution 3;

[0136] S3: Solution 1 and solution 3 are mixed and stirred at 45°C for 24 hours to obtain a precursor solution of a composite electrolyte. The precursor solution of the composite electrolyte is then mechanically coated with a coating thickness of 400 μm. After coating, vacuum curing is performed at 70°C for 24 hours to obtain a composite solid electrolyte membrane with a thickness of 70 μm.

[0137] The composite solid electrolyte membrane prepared above was assembled into a battery, and stainless steel sheets were used as positive and negative electrodes to assemble SS||SS batteries; metal lithium was used as the negative electrode and stainless steel was used as the positive electrode to assemble Li||SS batteries; metal lithium was used as the positive and negative electrodes to prepare Li||Li symmetric batteries; metal lithium was used as the negative electrode and NCM811 or LFP was used as the positive electrode to prepare Li||NCM811 / LFP full batteries. All operations were carried out in a glove box filled with argon.

[0138] Example 2

[0139] The synthesis method and preparation conditions are the same as those in Example 1, except that the temperature of preparing solution 1, solution 2, solution 3, and the precursor solution of the composite electrolyte is 40°C.

[0140] Example 3

[0141] The synthesis method and preparation conditions are the same as those in Example 1, except that tributylmethylammonium chloride is used to replace DODAC.

[0142] Example 4

[0143] The synthesis method and preparation conditions are the same as those in Example 1, except that bismuth phosphate is used to replace Bi(NO3)3·5H2O.

[0144] Example 5

[0145] The synthesis method and preparation conditions are the same as those in Example 1, except that bismuth acetate is used to replace Bi(NO3)3·5H2O.

[0146] Example 6

[0147] The synthesis method and preparation conditions are the same as those in Example 1, except that dimethyldioctadecylammonium iodide is used to replace DODAC.

[0148] Example 7

[0149] The synthesis method and preparation conditions are the same as those in Example 1, except that didodecyl dimethyl ammonium bromide is used to replace DODAC.

[0150] Comparative Example 1

[0151] Preparation of BiOCl

[0152] Simple BiOCl three-dimensional nanospheres were synthesized under the condition that the mass ratio of NH4Cl to Bi(NO3)3·5H2O was 1:3. At 25°C, 3g of Bi(NO3)3·5H2O and 3ml of concentrated nitric acid were added to 40ml of deionized water and stirred vigorously to obtain solution 1. Subsequently, 1g of NH4Cl was dissolved in 10mL of deionized water to obtain solution 2, and solution 2 was added to solution 1. After stirring for 8h, the suspension was collected, centrifuged at 5000rpm, and washed with deionized water and ethanol for 3 times, dried and ground under a vacuum environment at 333K to obtain three-dimensional nanospheres of BiOCl, which were sieved through 200 mesh and stored in a glove box.

[0153] PVDF and DMF were stirred at a speed of 500 rpm for 12 hours at a mass ratio of 1:10 to obtain a PVDF solution, which was marked as solution 1; LiTFSI was added to solution 1 and stirred at a speed of 500 rpm for 6 hours, which was marked as solution 2, wherein the mass ratio of LiTFSI to PVDF was 1:1;

[0154] Adding BiOCl to solution 2, stirring at 400 rpm for 12 hours at 45°C to obtain solution 3, wherein the mass ratio of BiOCl to PVDF is selected from 0.1:1;

[0155] The uniformly mixed solution 3 was subjected to ultrasonic treatment, each time for 10 minutes, and then allowed to stand for 2 minutes, for a total of 30 minutes. After the ultrasonic treatment, the ultrasonicated solution 3 was poured onto a glass plate, and the scraper thickness was adjusted to 300 μm for coating. After the coating was completed, the solution was allowed to stand for 2 hours, and then vacuum dried at 70°C for 24 hours to obtain a composite solid electrolyte membrane with a thickness of 50 μm.

[0156] The composite solid electrolyte membrane prepared in Comparative Example 1 was used to assemble a battery. Stainless steel sheets were used as positive and negative electrodes to assemble SS||SS batteries; metal lithium was used as the negative electrode and stainless steel was used as the positive electrode to assemble Li||SS batteries; metal lithium was used as the positive and negative electrodes to prepare Li||Li symmetric batteries; metal lithium was used as the negative electrode and NCM811 was used as the positive electrode to prepare Li||NCM811 full batteries. All operations were performed in a glove box filled with argon.

[0157] Comparative Example 2

[0158] The synthesis method and preparation conditions are the same as those in Example 1, except that the temperature of preparing solution 1, solution 2, solution 3, and the precursor solution of the composite electrolyte is 30°C.

[0159] Comparative Example 3

[0160] The synthesis method and preparation conditions are the same as those in Example 1, except that ammonium chloride is used instead of DODAC.

[0161] Comparative Example 4

[0162] The synthesis method and preparation conditions are the same as those in Example 1, except that in step S2, 0.5 g of PVDF and 0.5 g of LiTFSI are added to solution 1.

[0163] Comparative Example 5

[0164] Comparative Example 5 was prepared under the same conditions as Example 1, except that in step S1, bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and DODAC were dissolved in the same DMF to obtain solution 1, and in step S2, LiTFSI and PVDF were dissolved in solution 1 to obtain a precursor solution of a composite electrolyte, and then the precursor solution of the composite electrolyte was mechanically coated with a coating thickness of 400 μm. After coating, it was vacuum cured at 70°C for 24 hours to obtain a composite solid electrolyte membrane with a thickness of 70 μm.

[0165] The composite solid electrolyte membrane prepared above was assembled into a battery, and stainless steel sheets were used as positive and negative electrodes to assemble SS||SS batteries; metal lithium was used as the negative electrode and stainless steel was used as the positive electrode to assemble Li||SS batteries; metal lithium was used as the positive and negative electrodes to prepare Li||Li symmetric batteries; metal lithium was used as the negative electrode and NCM811 or LFP was used as the positive electrode to prepare Li||NCM811 / LFP full batteries. All operations were carried out in a glove box filled with argon.

[0166] Test Method

[0167] The electrochemical window of the electrolyte was determined by linear sweep voltammetry (LSV): Li||SS battery was used as the battery to be tested, with a voltage of 1 mV s -1 The scan rate is slowly scanned from the battery open circuit voltage to the positive voltage to obtain the electrochemical window.

[0168] Electrochemical impedance spectroscopy (EIS) was used to measure the ionic conductivity of the electrolyte. The SS||SS battery was used as the battery to be tested for electrochemical impedance spectroscopy, with a frequency range of 0.1-10 -6 Hz, amplitude 10mV. After the test, the battery was disassembled to measure the thickness of the solid electrolyte, and the electrolyte ion conductivity was calculated based on the AC impedance results.

[0169] Take the Li||Li symmetrical battery as the battery to be tested: the battery is subjected to constant current density charge and discharge test. The test conditions are to apply a certain current density to it, charge it for one hour, and then discharge it for one hour for a cycle.

[0170] Take Li||NCM811 full battery as the battery to be tested: the battery is charged and discharged cycled at a certain current density to explore the battery stability, where the voltage range is 3.0V-4.3V.

[0171] The test results are shown in Table 1

[0172] Table 1

[0173]

[0174] As can be seen from Table 1, Examples 1-7 show better β-phase content, crystallinity and cycle capacity retention rate than Comparative Examples 1-5, indicating that the method for in situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane can effectively utilize the characteristics of bismuth salt and organic halide containing alkyl and quaternary ammonium cations being soluble in organic solvents at 40°C-60°C, thereby realizing the in situ growth of bismuth oxyhalide on the PVDF base, thereby achieving uniform dispersion of bismuth oxyhalide in the composite solid electrolyte membrane, promoting the conversion of β-phase, improving battery cycle performance, and optimizing battery capacity retention rate.

[0175] Figure 1 The XRD pattern of BiOCl synthesized in Comparative Example 1 is shown in FIG. Figure 2 The XRD pattern of the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane synthesized in Example 1 is shown in FIG. 1 . It can be observed that in both Example 1 and Comparative Example 1, we successfully synthesized BiOCl. When BiOCl was added at the same time, Comparative Example 1 exhibited lower β-phase content and cycle performance and electrochemical window ( Figure 5 ), indicating that the preparation method proposed in this scheme can effectively avoid the agglomeration problem of bismuth oxyhalide and achieve uniform distribution of bismuth oxyhalide in the PVDF matrix.

[0176] Furthermore, the present scheme also discusses the effect of reaction temperature on the present scheme. It can be observed that when the reaction temperature of S1, S2, and S3 is 30°C (Comparative Example 2), DODAC cannot be dissolved in DMF as a solvent, and therefore the composite solid electrolyte membrane cannot be prepared in situ. When NH4Cl is used to replace DODAC (Comparative Example 3), since NH4Cl is difficult to dissolve in DMF, the same result as in Comparative Example 2 is presented, and the preparation of the composite solid electrolyte membrane fails. Therefore, in the present scheme, it is very important to ensure that the reaction temperature of S1, S2, and S3 is under heating conditions and to select organic halides containing alkyl and quaternary ammonium cations at the same time.

[0177] Comparative Example 4 We discussed the case of dissolving a polymer containing PVDF segments and LiTFSI in solution 1. It can be observed that compared with Example 1, the cycle capacity retention rate of Comparative Example 4 is significantly lower. This may be due to the lack of a pre-formed cross-linked network structure between the organic halide containing alkyl and quaternary ammonium cations and the polymer containing PVDF segments. The bismuth salt is difficult to be directly anchored on the cross-linked network, making it impossible for the subsequent in-situ grown bismuth oxyhalide to be evenly distributed in the composite solid electrolyte membrane.

[0178] In Comparative Example 5, we simultaneously dissolved the bismuth salt and the organic halide containing alkyl and quaternary ammonium cations in the organic solvent in the initial stage. This may lead to the immediate generation of bismuth oxyhalide, but the inability to generate bismuth oxyhalide in situ while forming the composite solid electrolyte membrane, resulting in the bismuth oxyhalide still not being evenly distributed in the PVDF matrix, thereby affecting the cycle performance of the battery.

[0179] In order to further explore the effect of temperature on this scheme, in Examples 1-2, we selected different temperatures for experiments. It can be observed that when the reaction temperature in S1, S2, and S3 is 45°C, Example 1 exhibits a better cycle capacity retention rate. This may be because the reaction temperature of 45°C helps to further promote the dissolution of DODAC and Bi(NO3)3·5H2O in DMF, allowing the subsequent generation of more evenly distributed bismuth oxyhalides.

[0180] In Examples 1, 3, 6, and 7, we discussed the effect of the structure of organic halides containing alkyl and quaternary ammonium cations on their performance. It can be observed that Examples 1, 6, and 7 with symmetrical structures exhibited better cycle capacity retention rates. This may be because organic halides with symmetrical structures can promote better dispersion of bismuth salts and the generated bismuth oxyhalides. Therefore, Examples 1, 6, and 7 exhibited better cycle capacity retention rates.

[0181] In order to confirm the scope of application, this scheme further explores the influence of bismuth salts on its performance. It can be observed that in Examples 1, 4, and 5, the cycle capacity retention rates all have good performance, indicating that the preparation method provided in this scheme can be applied to different bismuth sources, especially oxygen-containing acid bismuth salts and organic acid bismuth salts. When oxygen-containing acid bismuth salts and organic acid bismuth salts are selected, Examples 1, 4, and 5 all show good cycle performance.

[0182] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A bismuth oxyhalide-PVDF-based composite solid electrolyte membrane, characterized in that: The β-phase percentage of PVDF in the composite solid electrolyte membrane is selected from 60%-70%, and the crystallinity is 20%-25%, wherein the general formula of bismuth oxyhalide is BiOX, wherein Bi is bismuth element, O is oxygen element, X is halogen element, and the halogen element is selected from any one of Cl, Br, I, and F. The mass ratio of bismuth oxyhalide to the polymer containing PVDF chain segments is selected from (0.01-0.5):

1.

2. The bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 1, characterized in that: The bismuth oxyhalide is selected from any one of BiOCl, BiOBr, BiOI and BiOF; Preferably, the bismuth oxyhalide is selected from BiOCl; Preferably, the raw materials of the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane include bismuth salt, organic halide containing alkyl and quaternary ammonium cations, polymer containing PVDF chain segments, and lithium salt.

3. A method for preparing the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 1, characterized in that: The steps include: S1: dissolving a bismuth salt and an organic halide containing an alkyl group and a quaternary ammonium cation in an organic solvent respectively under heating according to a stoichiometric ratio to obtain a solution 1 and a solution 2; S2: dissolving a polymer containing a PVDF segment and a lithium salt in solution 2 in a heated state according to a stoichiometric ratio to obtain solution 3; S3: After mixing and reacting solution 1 and solution 3 under heating, a precursor solution of a composite electrolyte is obtained, and the precursor solution of the composite electrolyte is coated and cured to obtain a composite solid electrolyte membrane.

4. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In the step S1, the molar ratio of the bismuth salt to the organic halide containing an alkyl group and a quaternary ammonium cation is selected from 1:(2-2.5); Preferably, in step S1, the mass ratio of the total mass of the bismuth salt and the organic halide containing alkyl and quaternary ammonium cations to the organic solvent is selected from (0.01-0.5): (5-20); Preferably, in step S1, the bismuth salt is selected from any one of an oxygen-containing acid bismuth salt and an organic acid bismuth salt.

5. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In the step S1, the organic halide containing an alkyl group and a quaternary ammonium cation is selected from any one of the organic halide containing a C2-C20 alkyl group and a quaternary ammonium cation; Preferably, in step S1, the organic halide containing a C2-C20 alkyl group and a quaternary ammonium cation is selected from an organic halide having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation; Preferably, in step S1, the organic halide having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is selected from an ammonium halide salt having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation; Preferably, the ammonium halide salt having a symmetrical structure and containing a C4-C20 alkyl group and a quaternary ammonium cation is selected from dioctadecyl dimethyl ammonium chloride Didodecyl dimethyl ammonium chloride Dimethylditetradecylammonium chloride Dioctadecyl dimethyl ammonium bromide Dimethyldioctadecylammonium iodide Tetrabutylammonium chloride Tetrapentylammonium chloride Tetrabutylammonium iodide Tetrahexylammonium iodide Tetraheptylammonium iodide Any one of; Preferably, in step S1, when the bismuth salt and the organic halide containing an alkyl group and a quaternary ammonium cation are dissolved in an organic solvent respectively, the heating temperature is selected from 40° C. to 60° C.

6. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In the step S2, the mass ratio of the polymer containing PVDF segments to the lithium salt is selected from 1:(0.25-2); Preferably, the mass ratio of the polymer containing PVDF segments to the organic solvent is selected from 1:(5-20); Preferably, in step S2, the polymer containing PVDF segments is selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and a mixture of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP); Preferably, in the mixture of PVDF and PVDF-HFP, the mass ratio of PVDF to PVDF-HFP is selected from 3:1; Preferably, the lithium salt is selected from any one or more of LiPF6, LiF, LiBF4, LiTFSI, LiCl, Li2SO4, LiOAc, LiNO3, LiPO2F2, LiCF3SO3, Li2CO3, LiFSI, LiBOB, and LiDFOB; Preferably, the lithium salt is selected from LiTFSI; Preferably, the organic solvent is selected from any one or more of amide solvents, pyrrolidone solvents and ether solvents.

7. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In the step S2, when the polymer containing PVDF segments and lithium salt are dissolved in the solution 1 containing bismuth salt, the heating temperature is selected from 40° C. to 60° C., and the heating time is greater than or equal to 6 hours; Preferably, in step S2, when the polymer containing PVDF segments and lithium salt are dissolved in solution 1 containing bismuth salt, the heating temperature is selected from 40° C.-60° C., and the heating time is selected from 6 h-10 h.

8. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In step S3, the temperature for the mixed reaction of solution 1 and solution 3 is selected from 40° C. to 60° C., and the mixed reaction time is selected from 22 h to 26 h.

9. The method for in-situ preparation of bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to claim 3, characterized in that: In the step S3, the coating method is mechanical coating; Preferably, the mechanical coating step is: pouring the solution 3 onto a glass plate, and then adjusting the scraper thickness to 300 μm for uniform coating; Preferably, the curing time is selected from 1.5h-3h; Preferably, the vacuum drying temperature in step S3 is selected from 60°C to 80°C; Preferably, the vacuum drying time in step S3 is selected to be greater than or equal to 20 hours.

10. A diaphragm, an electrode, a battery, an electrochemical device, an electrical device, an energy storage device, characterized in that: A bismuth oxyhalide-PVDF-based composite solid electrolyte membrane comprising the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane according to any one of claims 1 to 2 or the bismuth oxyhalide-PVDF-based composite solid electrolyte membrane prepared by the method according to any one of claims 3 to 9; Preferably, the battery is selected from any one of a solid-state battery and a semi-solid-state battery.

Citation Information

Patent Citations

  • Inorganic filler powder, solid electrolyte, preparation method thereof and battery

    CN113036214A

  • Conductive polymer coated bismuth oxychloride positive electrode material for chloride ion battery and preparation method of conductive polymer coated bismuth oxychloride positive electrode material

    CN116969507A

  • Method for modifying bismuth oxyiodide-based composite solid polymer electrolyte and method for constructing lithium battery by using bismuth oxyiodide-based composite solid polymer electrolyte

    CN119069819A

  • BiOBr-MnO2 polymer film as well as preparation method and application thereof

    CN119281142A

  • Battery material and electrode material

    EP3929228A1